Management of constipation in long-term care hospitals and its ward manager and organization factors - Manami Takaoka; Ayumi Igarashi; Asako Futami; Noriko Yamamoto-Mitani (BMC, 2020)
Abstract Background Studies examining organizational factors that may influence constipation management in long-term care (LTC) hospitals are lacking. This study aimed to clarify the practice of constipation management in LTC hospitals and to explore its factors, including ward manager's perception, organizational climate, and constipation assessment. Methods In this cross-sectional questionnaire survey of ward managers and staff nurses working in LTC wards, we determined daily assessment and practices regarding constipation management. We also conducted multivariate analyses to examine factors related to constipation management. Results There was a 20% response rate to the questionnaire. Nearly all LTC wards routinely assessed bowel movement frequency; other assessments were infrequent. Laxatives were used, but the use of dietary fiber and probiotic products was implemented in only 20-30% of wards. The implementation of non-pharmacological management and adequate use of stimulant laxatives were positively associated with the ward manager's belief and knowledge, organizational climate, the existence of nursing records for constipation assessment, planned nursing care for constipation, and organized conferences and in-hospital study sessions on constipation management. Conclusion Areas to improve constipation management in LTC hospitals include altering the ward manager's perception, improving hospital's organizational climate, and introducing standardized assessment/care planning systems.